FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG - Yuliastina, Mellani; Rahmah, Siti Aulia Nur; Nor, Wahyudin; Lesmanawati, Dewi (Universitas Lambung Mangkurat, 2023)
The intense competition within the capital market has prompted companies going public to enhance the caliber of their financial statements and hasten the release of audited financial reports. The purpose of this research is to evaluate and scrutinize the influence of factors such as audit tenure, corporate governance as measured by the presence of an independent board of commissioners, institutional ownership and managerial ownership, financial hardship, and audit capacity pressure on the delay of audit reports. The research population is comprised of infrastructure, utility, and transportation companies that were registered on the IDX during 2016-2019. Employing purposive sampling techniques, a sample of 21 companies was selected. The outcomes of the research indicate that audit tenure, institutional ownership, and financial difficulty have an impact on the delay of audit reports, while the existence of independent commissioners, managerial ownership, and audit capacity pressure do not have any effect on the delay of audit reports.